A formação desportiva no ordenamento jurídico brasileiro - Zainaghi, Luis Guilherme Krenek (2019)
This dissertation will study sports formation in Brazil. Not infrequently, young athletes (around 16 to 18 years old) compete in high-level competitions. Thus, it aims to understand the legal relationship of these athletes (especially soccer) with their clubs, because in some cases, sports formation goes beyond legal limits and becomes a true form of child labor. In order to do so, we studied the origin of the sports, as well as the work of children and adolescents in society, and analyzed the current legislation on the subject, and finally, comparing sports formation in Brazil with other countries. All research was carried out using analysis of legislation, doctrine and jurisprudence